2014
DOI: 10.1016/j.jaac.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse, Depression, and Methylation in Genes Involved With Stress, Neural Plasticity, and Brain Circuitry

Abstract: Objectives Determine if epigenetic markers predict dimensional ratings of depression in maltreated children. Method A Genome-wide methylation study was completed using the Illumina 450K BeadChip array in 94 maltreated and 96 non-traumatized children with saliva-derived DNA. The 450K BeadChip does not include any methylation sites in the exact location as sites in candidate genes previously examined in the literature, so a test for replication of prior research findings was not feasible. Results Methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
230
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(249 citation statements)
references
References 59 publications
13
230
2
4
Order By: Relevance
“…The probes on this array are not evenly spaced throughout the genome, and are enriched in specific regions. These regions do not align with DNA methylation sites commonly studied, such as NR3C1, as discussed in Weder et al 52 , or any sites previously examined in these infants. As a result of this, we were unable to validate previous associations identified between specific hypothesis-driven regions quantified through pyrosequencing and infant neurobehavior.…”
Section: Discussionmentioning
confidence: 60%
“…The probes on this array are not evenly spaced throughout the genome, and are enriched in specific regions. These regions do not align with DNA methylation sites commonly studied, such as NR3C1, as discussed in Weder et al 52 , or any sites previously examined in these infants. As a result of this, we were unable to validate previous associations identified between specific hypothesis-driven regions quantified through pyrosequencing and infant neurobehavior.…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, in rhesus macaques, the broad impact of maternal rearing in the first year of life on DNA methylation was seen in both the prefrontal cortex and T cells, supporting the hypothesis that the response to early-life adversity is system-wide and genome-wide and persists to adulthood [41 ]. A handful of papers have now shown changes in DNA methylation in peripheral blood cells with early trauma in humans on a genome-wide level [42][43][44]. Suderman et al specifically reported differential methylation in promoter regions of loci encoding microRNAs (miRNA) [43], in line with other studies showing the importance of miRNAs in modulating the stress response [45,46].…”
Section: Specific Versus Global Changesmentioning
confidence: 71%
“…As such, neuropsychiatric disorders which develop during adulthood are most likely caused by a combination of pre-existing genetic and epigenetic vulnerability factors and alterations that are caused as a consequence of adult life stress exposure itself (Jirtle & Skinner 2007), as suggested by the diathesis-stress model for psychiatric illnesses (Monroe & Simons 1991) and the three-hit concept of vulnerability to stress-related mental disorders (Daskalakis et al 2013). In line with this idea of differential (pre-existing) epigenetic patterns reflecting vulnerability, DNA methylation of SKA2 and BDNF prior to trauma exposure was found to predict suicidal behaviour and PTSD symptomatology (Kang et al 2013, Kaminsky et al 2015, Clive et al 2016, while methylation of SLC6A4 (Swartz et al 2016) and GRIN1 (Weder et al 2014), which encodes subunit zeta-1 of the N-methyl-d-aspartate (NMDA) glutamate receptor, predicted depression. Furthermore, other human studies have linked the basal state of the DNA methylome to substance abuse (Andersen et al 2015), aggression (Schechter et al 2017), and depressive behaviour (Zhao et al 2013).…”
Section: Animal Studiesmentioning
confidence: 95%